Finite difference methods : theory and applications : 7th International Conference, FDM 2018, Lozenetz, Bulgaria, June 11-16, 2018, Revised selected papers /: theory and applications : 7th International Conference, FDM 2018, Lozenetz, Bulgaria, June 11-16, 2018, Revised selected papers. (2019) - Unknown
No abstract available